Mental Disorders and Their Association With Disability Among Internally Displaced Persons and Returnees in Georgia. Issue 5 (October 2014) - Makhashvili, Nino; Chikovani, Ivdity; McKee, Martin; Bisson, Jonathan; Patel, Vikram; Roberts, Bayard
<x xml:space="preserve">Abstract</x> There remains limited evidence on comorbidity of mental disorders among conflict‐affected civilians, particularly internally displaced persons (IDPs) and former IDPs who have returned to their home areas (returnees). The study aim was to compare patterns of mental disorders and their influence on disability between IDPs and returnees in the Republic of Georgia. A cross‐sectional household survey was conducted with adult IDPs from the conflicts in the 1990s, the 2008 conflict, and returnees. Posttraumatic stress disorder (PTSD), depression, anxiety, and disability were measured using cut scores on Trauma Screening Questionnaire, Patient Health Questionnaire 9, Generalised Anxiety Disorder 7, and the WHO Disability Assessment Schedule 2.0. Among the 3, 025 respondents, the probable prevalence of PTSD, depression, anxiety, and comorbidity (>1 condition) was 23.3%, 14.0%, 10.4%, 12.4%, respectively. Pearson correlation coefficients (p < .001) were .40 (PTSD with depression), .38 (PTSD with anxiety), and .52 (depression with anxiety). Characteristics associated with mental disorders in regression analyses included displacement (particularly longer‐term), cumulative trauma exposure, female gender, older age, poor community conditions, and bad household economic situation; coefficients ranged from 1.50 to 3.79. PTSD, depression, anxiety, and comorbidity were associated with increases in disability of 6.4%, 9.7%, 6.3%, and 15.9%, respectively. A high burden of psychiatric symptoms and disability persist among conflict‐affected persons in Georgia.